Case Report: Clinical application of an in vitro prenylation assay in the diagnosis of an early-onset case of mevalonate kinase deficiency harbouring a novel MVK variant - Burleigh, Alice; Kul Cinar, Ovgu; Torpiano, Paul; Munoz, Marcia A.; Abell-King, Charlotte; Rogers, Michael J.; Eleftheriou, Despina; Brogan, Paul A. (Frontiers in Pediatrics, 2026)
Mevalonate kinase deficiency (MKD) is a systemic autoinflammatory disease caused by biallelic mutations in MVK. Individuals with MKD present with a recurrent fever syndrome, often including a skin rash, gastrointestinal symptoms and lymphadenopathy. The severity depends on the residual enzyme activity, which can be measured using an assay to confirm diagnoses in cases with non-confirmatory/novel MVK genotype. However, the assay is not widely available and utilises radioisotope, limiting its use in routine clinical care. More recently, the accumulation of unprenylated Rab GTPases in peripheral blood mononuclear cells, a downstream consequence of mevalonate kinase deficiency, has been described as an alternative diagnostic biomarker of MKD. We describe the utility of the Rab prenylation assay for the diagnostic workup of an infant with a novel MVK genotype presenting with fulminant autoinflammation. A seven-week-old girl, born to non-consanguineous White British parents, presented with features of haemophagocytic lymphohistiocytosis (HLH): fever, hepatosplenomegaly, bicytopenia, hyperferritinaemia, transaminitis, raised lactate dehydrogenase and C-reactive protein. She had a three-week history of fever and a generalised erythematous rash, with negative infectious work-up. Gene panel sequencing revealed biallelic trans MVK variants: MVK: c.151C > T (p.L51P), a previously described pathogenic variant; and MVK: c.1027C > T (p.L343P), a novel variant. A mevalonate kinase enzyme activity assay, requested via the reference laboratory in Amsterdam, confirmed 3% residual activity in the patient, consistent with MKD. However, this test result took 21 days to return, therefore a prenylation assay was performed in the meantime, revealing clear accumulation of Rab proteins in a blood sample from the patient, thus confirming pathogenicity of the variants and securing the diagnosis of MKD. The turnaround time of this assay was 2 days. We demonstrate the use of a protein prenylation assay in the diagnosis of a very early-onset case of MKD presenting with HLH, with a novel MVK genotype. This assay is quicker and simpler to set up in routine clinical care than measurement of mevalonate kinase activity, the current gold standard for MKD diagnosis. This case demonstrates the clinical utility of the prenylation assay for specific and timely MKD diagnosis and expands the genotypic spectrum of MKD.